Power transmission and motion control (PTMC 2005) : / [compact disc] - Bath Workshop on Power Transmission and Motion Control (2005 : University of Bath); Johnston, D. N. (D. Nigel); Burrows, C. R. (Clifford Robert); Edge, K. A. (Kevin A.) (Hoboken, NJ : John Wiley & Sons, 2005)
20